Stable LATP/LAGP double-layer solid electrolyte prepared via a simple dry-pressing method for solid state lithium ion batteries. Issue 95 (28th September 2016) - Zhao, Erqing; Ma, Furui; Guo, Yudi; Jin, Yongcheng
Abstract : A LATP/LAGP bi-layer structured solid electrolyte has been prepared via a simple dry-pressing and post-calcination process, which exhibits high electrical conductivity and excellent stability in air as well as high chemical stability against Li. Abstract : In this paper, a NASICON-type Li1.3 Al0.3 Ti1.7 (PO4 )3 (LATP)/Li1.3 Al0.3 Ge1.7 (PO4 )3 (LAGP) bi-layer structured solid state electrolyte was successfully prepared via a simple dry pressing and post-calcination method. By adjusting the sintering temperature for LAGP starting materials, a dense and smooth LATP/LAGP double-layer solid state electrolyte with no defects was obtained. This electrolyte sample exhibits a high electrical conductivity of 3.4 × 10 −4 S cm −1 and a negligible electronic conductivity of 9.6 × 10 −9 S cm −1 at room temperature. In addition, the LATP/LAGP electrolyte also shows an excellent stability in air as well as chemical stability against Li. Moreover, an assembled LiFePO4 /LATP–LAGP/Li coin-type battery employing LATP/LAGP as the solid state electrolyte can be suitably charged and discharged at a current rate of 0.1C at room temperature, and its low charge–discharge capacities are mainly attributed to the high electrolyte/electrode interfacial resistance of the cell. These results suggest that the LATP/LAGP bi-layer electrolyte can be an alternative electrolyte for all-solid-state lithium-ion batteries.